Study of Physical Properties of Complex Scalar Field at Finite Density - Phat, Tran Huu; Thuy, Bui Thi Phuong (Communications in Physics, 2011)
The physical properties of a relativistic model for complex scalar field at finite density are studied. It is shown that the boson is condensed when the critical chemical potential is equal to the boson mass in vacuum and the system undergoes the phase transition from normal to superconducting states. The latter state is signaled by the manifestations of the Meissner effect and the Abrikosov vortices in the presence of an electromagnetic field. Moreover, the boson condensate is separated by a topologically stable domain wall.